Peran Kiai Iskandar Umar Abdullatif di Krian Sidoarjo - Muhammad Akbar Firdaus (Qurthuba: The Journal of History and Islamic Civilization, 2021)
Abstract: This study seeks to explore the autobiography of a character, namely Kiai Iskandar Umar Abdullatif in shaping the morals of the Krian community, Sidoarjo, the period 1985-2010. Society has a collective character that can be formed or changed to become more mature---in the assumption that some people are "better"---including the people of Krian, of course in a short period. Kiai Iskandar Umar Abdullatif is someone who seems to have this assumption because he is an important scholar in changing the character of the Krian community to become more "Islamic". The aim of this research is; first, to photograph the figure of Kiai Iskandar Umar Abdullatif in shaping the Islamic character of the Krian community by using Weber's leadership theory. Second, the changes in the pre-and post-formation Krian society in the 1985-2010 period. This research uses historical research methods and community anthropological approaches. The results of this study revealed that Kiai Iskandar Umar Abdullatif made several efforts to shape the Islamic character of the Krian community. He founded the Darul Falah Islamic Boarding School to build the character of the children of the Krian community, opened branch boarding schools from the mass marriage program for his satri students, held scientific assemblies in the community, and became a figure of ulama whose fatwas were obeyed by the community. This study also found a change in the character of the Krian community to become more Islamic since the existence of the Darul Falah Islamic Boarding School. People who initially liked to lose money, gamble, drink, and other un-Islamic matters turned out to be fond of the routine activities of the Koran, congregational prayers, diba'iyah, sholawat, and others. Keywords: character, Kiai Iskandar Umar Abdullatif, Krian, society